2019
DOI: 10.1038/s41467-019-10165-5
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical safety study of a combined therapeutic bone wound dressing for osteoarticular regeneration

Abstract: The extended life expectancy and the raise of accidental trauma call for an increase of osteoarticular surgical procedures. Arthroplasty, the main clinical option to treat osteoarticular lesions, has limitations and drawbacks. In this manuscript, we test the preclinical safety of the innovative implant ARTiCAR for the treatment of osteoarticular lesions. Thanks to the combination of two advanced therapy medicinal products, a polymeric nanofibrous bone wound dressing and bone marrow-derived mesenchymal stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…In order to improve its mechanical endurance and biocompatibility for orthopedic application, PCL is often blended with either other polymers or ceramics, such as HAp [27,28]. We recently developed a two-compartmented scaffold for the osteoarticular regeneration: the first functionalized nanofibrous compartment for the subchondral bone regeneration; and a second hydrogel-based compartment mixed with human adult bone marrow-derived mesenchymal stem cells for the articular cartilage [7]. This study demonstrated that it is possible to recreate mineralization gradients physiologically present at the osteochondral level by using adult mesenchymal stem cells, an alginate hydrogel, and nanofibrous membranes of synthetic PCL polymer or collagen equipped with nanoreservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to improve its mechanical endurance and biocompatibility for orthopedic application, PCL is often blended with either other polymers or ceramics, such as HAp [27,28]. We recently developed a two-compartmented scaffold for the osteoarticular regeneration: the first functionalized nanofibrous compartment for the subchondral bone regeneration; and a second hydrogel-based compartment mixed with human adult bone marrow-derived mesenchymal stem cells for the articular cartilage [7]. This study demonstrated that it is possible to recreate mineralization gradients physiologically present at the osteochondral level by using adult mesenchymal stem cells, an alginate hydrogel, and nanofibrous membranes of synthetic PCL polymer or collagen equipped with nanoreservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, MSCs preferred to proliferate than to differentiate into chondrocytes in such condition. We and others have reported that hyaluronic acid could enhance chondrogenic differentiation [ 7 , 42 , 43 ]. Surprisingly, no active effect of HA was observed for the chondrogenic differentiation ( Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicated the preclinical safety of this www.advancedsciencenews.com www.advhealthmat.de new technology based on the international regulatory guidelines and requirements for phase I clinical trials. [90] Lin et al produced a biphasic construct based on viscoelastic PEGylated poly(glycerol sebacate) (PEGS). [91] The lower layer was the mesoporous bioactive glass (MBG) scaffold, which improved osteogenesis.…”
Section: Tgf-1 Bmp-2mentioning
confidence: 99%
“…More recently, Keller et al developed a bilayer innovative system, called ARTiCAR (ARTicular Cartilage and subchondRal bone implant), composed by two different compartments: i) a wound dressing made of nanofibrous poly‐ε‐caprolatone nanofunctionalized with BMP‐2 and ii) an injectable hydrogel of alginate and HA mixed with bone marrow‐derived MSC. [ 84 ] The ARtiCAR was implanted in a model of induced intra‐articular osteochondral defect in RH‐Foxn1 rnu/rnu nude rats or in sheep provided a correct subchondral bone formation and remodeling of the osteochondral defect with a good integration of the graft in the host tissue after 26 weeks. Considering the good results, the authors suggest the product for phase I clinical trials as a strategy to treat localized osteochondral defects.…”
Section: From Basic To Advanced Cartilage Models: New Strategies To Dmentioning
confidence: 99%